2010
DOI: 10.1007/s00296-010-1514-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of posture and pain in persons with benign joint hypermobility syndrome

Abstract: The objective of the present study is to compare and quantify the postural differences and joint pain distribution between subjects with benign joint hypermobility syndrome (BJHS) and the normal population. This observational, non-randomized, and controlled study was conducted at Rheumatology and Physical Medicine and Rehabilitation Medicine Departments of a tertiary care teaching hospital. Subjects comprise 35 persons with diagnosis of BJHS, and the control group was matched for age and sex. Reedco's Posture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…[6,7] Impaired joint proprioception can lead to poor postural control and balance in patients with HMS, as has been previously demonstrated by the research. [13,26] However, a review of the literature did not reveal any studies which have evaluated balance problems in FMS patients and their association with hypermobility. Furthermore, a connection between increased fall frequency due to balance problems in FMS has been previously shown, but the relationship between hypermobility and fall history has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Impaired joint proprioception can lead to poor postural control and balance in patients with HMS, as has been previously demonstrated by the research. [13,26] However, a review of the literature did not reveal any studies which have evaluated balance problems in FMS patients and their association with hypermobility. Furthermore, a connection between increased fall frequency due to balance problems in FMS has been previously shown, but the relationship between hypermobility and fall history has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study the result of the question about the localization of the disorders is as expected and as described in the literature [34,35]. Although the collected data on localization and type of disorders is the sum of all the problems ever mentioned over a period of 6 months, direct comparison between the three groups NM, HM-as and HM-s remains difficult.…”
Section: Discussionmentioning
confidence: 60%
“…A study which investigated the postures of patients with BJHS found significant differences between the patients with BJHS and the control group with regard to posture scores and pain [28]. All the clinical signs and symptoms evaluated under this study were significantly higher and New York posture rating test scores were significantly lower in patients with BJHS.…”
Section: Discussionmentioning
confidence: 71%